2007
DOI: 10.1364/oe.15.000473
|View full text |Cite
|
Sign up to set email alerts
|

High power passively Q-switched ytterbium fiber laser with Cr^4+:YAG as a saturable absorber

Abstract: We report an efficient high-peak-power and high-average-power passively Q-switched ytterbium fiber laser with a Cr(4+):YAG crystal as a saturable absorber in an external-resonator configuration. At an incident pump power of 17.5 W, the passively Q-switched fiber laser produces an average power greater than 6.2 W with a pulse repetition rate of 48 kHz. The output pulses noticeably display a mode-locking phenomenon that leads to the maximum peak power to be higher than 20 kW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The full-width-half-maximum (FWHM) width of each individual peak was 1.0ns. The pulse profiles are similar to profiles that others have reported in passively Q-switched ytterbium fiber lasers [10,11], except that we observed significant fluctuations in the energy distribution between the peaks (not stable mode locking). The peak UV power exceeded 8kW, and the calculated UV peak intensity inside the BBO was ~1.6GW/cm 2 .…”
Section: Laser Performancesupporting
confidence: 88%
“…The full-width-half-maximum (FWHM) width of each individual peak was 1.0ns. The pulse profiles are similar to profiles that others have reported in passively Q-switched ytterbium fiber lasers [10,11], except that we observed significant fluctuations in the energy distribution between the peaks (not stable mode locking). The peak UV power exceeded 8kW, and the calculated UV peak intensity inside the BBO was ~1.6GW/cm 2 .…”
Section: Laser Performancesupporting
confidence: 88%
“…Figure 7 shows the variation of output pulse duration as a function of pump power. It shows that output pulse duration decreases with increase in input pump power, which is typically observed in Q-switched lasers 9 . Figure 8 shows the recorded output spectrum at the maximum output average power of 1.2 W. The output spectrum was peaked at 1068 nm with a FWHM linewidth of ~ 2.5 nm.…”
Section: Resultsmentioning
confidence: 62%
“…The other alternative is the passive Q-switching using a saturable absorber (SA) in laser cavity that offers much simpler design as compared to the active Q-switching. Huang et al reported recently a passively Q-switched Yb-doped fiber laser with Cr4+: YAG as an SA and achieve a high peak power of 20 kW [9]. However their laser consists of a Cr4+: YAG slab, three collimating and focus lenses, and a mirror that complicated substantially the laser cavity design.…”
Section: All-fiber Q-switched Yb-doped Fiber Lasermentioning
confidence: 99%